2005
DOI: 10.4314/sinet.v27i2.18244
|View full text |Cite
|
Sign up to set email alerts
|

A study on light trap catches of some rice pests in relation to meteorological factors

Abstract: The effect of meteorological factors on the population build up of green leafhopperNephotettix virescens Dist (Cicadellidae, Hemiptera), plant hoppers Cofana spectra Dist (Delphacidae, Hemiptera) and C. yasumatsui Young (Kolla mimica, Hemiptera) and rice gundhi bug Leptocoriza acuta Thunberg (Alydidae, Hemiptera) in rice growing season (July to November) was studied through light trap collection during ten years (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997). Maximum populations of Nephotettix vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
2
1
1
2
Order By: Relevance
“…The observation on the bug population also indicated that its appearance coincided with the flowering stage of the rice and the peak population was recorded only one week after its 1 st appearance and then after decrease in its population gradually took place which came down to zero on the last date of observation 11 Nov.2020. Similar results were also found by Sharma et al [18] , who observed Leptocorisa acuta Thunberg (Alydidae, Hemiptera) had maximum population in the second and third weeks of October during the aforesaid period. Singh et al [20] found that the maximum population of gundhi bud was recorded in the 43 rd SMW and 48 th SMW.…”
Section: Resultssupporting
confidence: 89%
“…The observation on the bug population also indicated that its appearance coincided with the flowering stage of the rice and the peak population was recorded only one week after its 1 st appearance and then after decrease in its population gradually took place which came down to zero on the last date of observation 11 Nov.2020. Similar results were also found by Sharma et al [18] , who observed Leptocorisa acuta Thunberg (Alydidae, Hemiptera) had maximum population in the second and third weeks of October during the aforesaid period. Singh et al [20] found that the maximum population of gundhi bud was recorded in the 43 rd SMW and 48 th SMW.…”
Section: Resultssupporting
confidence: 89%
“…From Table 2, we found out that short-horned grasshopper and rice gundhi bug had a negative insignificant correlation with an r value of -0.019 and -0.297 respectively. This is contrary to the findings of Sharma, et. al (2004).…”
Section: Average Rainfall and Insectscontrasting
confidence: 99%
“…They also found a significant negative correlation of the minimum temperature of L. acuta at Jagdalpur, India. But our findings were in status quo with the findings of Sharma et. al.…”
Section: Cardinal Temperature and Insectssupporting
confidence: 83%
“…Hoy en día, las lámparas de luz negra son ampliamente utilizadas para atrapar insectos en muchos cultivos a nivel mundial, la identificación y el conteo de las plagas del arroz capturadas con el empleo de TDL son importantes para monitorear su dinámica poblacional y poder llevar a cabo su pronóstico 33 . De esta manera, se puede determinar el período activo para controlar los insectos plaga bajo condiciones de campo, y poder evitar la pérdida de la cosecha del arroz causada por ellos 34 . Los factores meteorológicos juegan un papel importante en la abundancia estacional, distribución y acumulación de población de plagas de insectos.…”
Section: Introductionunclassified